The Relationship between Students’ Perceptions on Online Slack Application and Their Motivations in Writing Skill - Dian Ardiansah (Universitas Dian Nuswantoro, 2021)
Abstract. This present study aims to investigate the correlation between students’ perceptions of Slack application and their motivations in writing skills. An analysis of the research literature in perception and motivation as Wei and Elias (2011) theory revealed that students’ perceptions of classroom environment play an essential role in promoting students’ motivation in learning a language. A quantitative correlation was used in this present study. Thus, the data were collected by employing close-ended questionnaires towards Likert Scale technique. However, this study was conducted at one university in Tasikmalaya. The findings show that the correlation coefficient of rxy is 0.77. According to the strength of the correlation table, the rxy= 0.77 lies between 0.75 and 0.99 which means there is a correlation between students’ perceptions of online Slack application and their motivations in writing. This study suggested that Slack Application can be used as an alternative to facilitate students’ engagement in classroom activities.Keywords: ICT, Slack application, students’ motivation, writing skillAbstrak. Tujuan dari penelitian ini adalah untuk menyelidiki hubungan yang ada antara persepsi siswa tentang aplikasi Slack dan motivasi mereka dalam keterampilan menulis. Analisis literatur penelitian dalam persepsi dan motivasi sebagai teori Wei dan Elias (2011) mengungkapkan bahwa persepsi siswa tentang lingkungan kelas memainkan peran penting dalam mempromosikan motivasi siswa dalam belajar bahasa. Korelasi kuantitatif digunakan dalam penelitian ini. Dengan demikian, pengumpulan data dilakukan dengan menggunakan kuesioner tertutup terhadap teknik Skala Likert. Namun penelitian ini dilakukan di salah satu Universitas di Tasikmalaya. Hasil penelitian menunjukkan bahwa rxy memiliki koefisien korelasi sebesar 0,77. Berdasarkan tabel kekuatan hubungan, rxy = 0.77 berada di antara 0.75 dan 0.99 yang berarti hubungan tersebut sangat kuat. Studi ini menyarankan bahwa Slack Application dapat menjadi cara lain untuk memfasilitasi keterlibatan siswa dalam kegiatan kelas.Kata kunci: aplikasi Slack, ICT, keterampilan menulis, motivasi siswa